Praktek Tayamum dan Sholat Sebagai Upaya Proses Penyembuhan Pasien Rawat Inap di Rumah Sakit Tugu Ibu, Cimanggis Depok Tayamum and Prayer as an Effort for the Healing Process of Inpatients at Tugu Ibu Hospital, Cimanggis Depok - Sri Rahayu,; Ahmad Said Matondang, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Every individual who is experiencing pain has organ dysfunction, psychological discomfort, namely the patient's biological-psychological-social and spiritual disorders. Nurses are health workers for 24 hours dealing with inpatients who can help fulfill biological-psychological-social and spiritual needs. This community service program at Tugu Ibu Hospital by a team of Uhamka lecturers aims to provide education and guidance to nurses in meeting spiritual needs, including the practice of tayammum and prayer services for inpatients. The method used is the training conducted on July 21, 2021 through a virtual zoom meeting due to the Covid 19 pandemic and PPKM is still being implemented with participants from the nursing leadership, the Training and Education section and 34 nursing staff. The media used for education are materials in the form of ppt and pocket books that have been distributed prior to the training. The results of interviews with several informants who can represent other participants that participants understand and are motivated to help patients carry out tayammum and prayer. In August 2021, observations were carried out for 10 days in practice, not all treatment rooms were able to carry out the results of the training, especially the isolation room for Covid 19 patients. Suggestions for the Education and Training section to make a program mandatory fiqh training of patient worship and the nursing field should include tayamum and prayer assistance in planning and implementation nursing care